2021
DOI: 10.1080/16078454.2021.1889161
|View full text |Cite
|
Sign up to set email alerts
|

Persistence to hypomethylating agents and clinical and economic outcomes among patients with myelodysplastic syndromes

Abstract: Objectives: To evaluate hypomethylating agent (HMA) persistence in patients with myelodysplastic syndromes (MDS), and examine its association with healthcare resource utilization (HRU) and progression to acute myeloid leukemia (AML). Methods: A total of 2,400 adults diagnosed with MDS initiating HMAs were included from IBM MarketScan databases during 1/1/2011-3/31/2018. The index date was HMA initiation following MDS diagnosis. Patients were classified according to their persistence status by the end of a fixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Treatment failure among patients receiving HMA is common and can result in significant healthcare costs for those patients [ 3 , 21 ]. Some studies suggest that low persistence with HMA therapy (which worsens over time) may be a factor in poor outcomes in real‐world treatment [ 22 , 23 ]. A better understanding of the patient, carer, and clinician treatment preferences can help to understand why HMAs fail and the factors related to poor persistence.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment failure among patients receiving HMA is common and can result in significant healthcare costs for those patients [ 3 , 21 ]. Some studies suggest that low persistence with HMA therapy (which worsens over time) may be a factor in poor outcomes in real‐world treatment [ 22 , 23 ]. A better understanding of the patient, carer, and clinician treatment preferences can help to understand why HMAs fail and the factors related to poor persistence.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that adherence and persistence with HMA treatment may be associated with reduced HCRU in the long term. 16 , 18 While the survey did not evaluate HCRU and costs incurred by patients receiving oral DEC-C versus IV/SC HMAs, treatment with oral DEC-C at home could potentially reduce HCRU and related costs, while maintaining efficacy, due to fewer visits to healthcare facilities compared with parenteral HMA therapy. Reduced visits to healthcare facilities with oral DEC-C treatment could also potentially lead to savings in travel costs for patients and caregivers and costs related to work absenteeism and lost wages as observed in studies conducted in other disease areas.…”
Section: Discussionmentioning
confidence: 99%
“… 14 HMA underuse is also associated with a burden on healthcare resource utilization (HCRU), with higher total per-patient-per-month healthcare costs reported among patients who were non-persistent with HMAs compared with those who were persistent ($18,039 versus $13,893). 16 18 Previous studies on patients’ experiences with IV/SC HMA therapy have highlighted the treatment burden associated with parenteral HMA administration. 19 , 20 In a prior survey conducted in the United States, patients reported pain and anxiety before and during IV/SC HMA therapy, interference with daily activities, and logistical challenges related to IV/SC administration of HMAs.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8]10,13,14 Nonpersistence with HMAs is associated with a poorer prognosis, more rapid disease progression (including progression to AML), and higher healthcare resource use. 18,34,36 Therefore, it is important to understand the factors associated with treatment persistence, including the level of caregiver support and patients' expectations of and willingness to accept toxicity with HMAs. Moreover, educating patients that MDS itself can be lifethreatening, even without progression to AML, may facilitate better treatment persistence.…”
Section: Multidisciplinary Perspective: Considerations For Treatment ...mentioning
confidence: 99%
“…18,35 Not only can early discontinuation have a negative impact on treatment outcomes, including OS, but it can also result in significantly higher economic costs. 18,36 The healthcare costs associated with the management of patients with MDS following early discontinuation of HMA therapy are approximately $77,000 per patient during the first 6 months and $130,000 for the subsequent 12 months. 37 Furthermore, access to and persistence with parenteral HMAs are influenced by socioeconomic and clinical factors, including age, marital status, and comorbidities (Table 2).…”
Section: Introductionmentioning
confidence: 99%